The Role of Cultural and Institutional Distances in International Trade - Nguyen Tien Long; Nguyen Thi Gam; Vu Hong Van; Bui Hoang Ngoc (Ital Publication, 2023)
Despite the effectiveness of the observed barriers such as taxes and quotas to adjust bilateral trade, they are still not well supported by governments in general and the World Trade Organization in particular. Therefore, in recent years, unobserved barriers have been critical tools to modify the trade flows between nations worldwide. China’s exports account for a massive proportion of global trade. However, the role of cultural and institutional distance in China’s trade flow has not been much explored. This study analyzes the impact of cultural and institutional differences on China's exports between 2006-2017 by adopting a system-GMM estimator. The main findings are, first, that cultural and institutional differences between China and its trading partners reduce China's exports. Second, cultural and institutional distances have the strongest influence on China's exports to high-income countries, followed by low-income countries, and finally middle-income countries. Third, manufactured products are the most sensitive to cultural and institutional distances. Based on these findings, several policies for China, as well as for emerging economies in general, are suggested for reducing cultural and institutional distances and boosting their exports. Doi: 10.28991/ESJ-2023-07-02-015 Full Text: PDF